1378. Evaluation of the In vitro Activity of Meropenem-Vaborbactam Against Carbapenem-Resistant Enterobacteriaceae, Including Isolates Resistant to Ceftazidime–Avibactam. (26th November 2018) - Wilson, William R; Kline, Ellen; Jones, Chelsea; Morder, Kristin; Clancy, Cornelius J; Nguyen, M Hong; Shields, Ryan K
Abstract: Background: Meropenem-vaborbactam (M-V) is a novel antibiotic for treatment of carbapenem-resistant Enterobacteriaceae (CRE) infections. Our objective was to determine the in vitro activity of meropenem-vaborbactam against genetically-diverse CRE isolates, including those that have developed resistance to Ceftazidime–Avibactam (C-A). Methods: Minimum inhibitory concentrations (MICs) were determined for meropenem (MER), M-V, and C-A by reference broth microdilution (BMD) methods in triplicate. Vaborbactam and avibactam were tested at fixed concentrations of 8 and 4 µg/mL, respectively. Quality control strains were used and within expected ranges. Polymerase chain reaction (PCR) with DNA sequencing was used to detect resistance determinants, including Klebsiella pneumoniae carbapenemase (KPC) subtypes and porin mutations. Results: A total of 117 CRE isolates were tested, including K. pneumoniae ( Kp ; n = 83), E. cloacae ( n = 17), E. coli ( n = 10), and E. aerogenes ( n = 7). Seventy-nine percent harbored bla KPC . KPC subtypes included KPC-2 ( n = 32), KPC-3 ( n = 41), KPC-3 variants ( n = 16), and KPC [not typed] ( n = 4, all E. coli ). Among 74 K. pneumoniae, 95% had a premature stop codon in ompk35 and ompK36 genotypes included wild type ( n = 48), IS5 insertion ( n = 13), 135–136 DG duplication ( n = 9), and other mutations ( n = 4). The median (range) MICs for MER, C-A, and M-V were 8 (0.06 to ≥128), 1 (0.25 to ≥512), and 0.03 (0.015––16), respectively. Corresponding rates of susceptibility were 23, 84, and 98%, respectively. Fifty-three percent and 95% of C-A-resistant isolates were susceptible to MER and M-V, respectively. Among Kp, C-A MICs did not vary by KPC subtype or porin genotype. On the other hand, median M-V MICs were higher among KPC-2 than KPC-3 Kp (0.12 vs. 0.03; P = 0.002), and among Kp with ompK36 porin mutations compared with wild type (0.25 vs. 0.03; P < 0.001). Among Kp with KPC-3 variants ( n = 16), the median M-V MIC was 0.03 (0.015––2); 100% were M-V susceptible. Median M-V MICs did not vary by CRE species. Only two isolates were M-V resistant, both were E. cloacae that did not harbor bla KPC . Conclusion: M-V demonstrates high rates of in vitro susceptibility against diverse CRE isolates, including those that are resistant to C-A. As this agent is introduced into the clinic, it will be important to identify K. pneumoniae isolates harboring KPC-2 with ompK36 porin mutations that demonstrate higher MICs. Disclosures: M. H. Nguyen, Merck: Grant Investigator, Research grant. Astellas: Grant Investigator, Research grant.